Preparation method of crystal-level terbium trifluoride
Through a multi-step method, including the preparation of high-purity terbium carbonate and the secondary fluorination treatment of terbium trifluoride, the problems of low purity and equipment corrosion in the existing terbium trifluoride preparation methods are solved, and the production of high-purity terbium trifluoride is achieved.
Patent Information
- Application Number
- CN202411599114.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-04-22
AI Technical Summary
The existing terbium trifluoride preparation methods have problems of low purity and serious equipment corrosion, resulting in the low purity of terbium trifluoride produced.
A multi-step process including the preparation of high purity terbium carbonate and terbium trifluoride is used. The specific steps include dissolving high-purity hydrated terbium nitrate crystals and reacting with ammonium carbonate to produce high-purity terbium carbonate, and then reacting with electronic grade hydrofluoric acid to obtain terbium trifluoride synthetic liquid, which is centrifuged, washed with water and secondary fluorination treatment, and finally obtaining high-purity terbium trifluoride through gradient drying.
The purity of terbium trifluoride is achieved to reach more than 99.99%, meets the crystal grade standards, and avoids equipment corrosion problems, improves the purity of the product and the safety of the production process.
Smart Images

Figure CN119858936A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing crystal-grade terbium trifluoride. Background Art
[0002] Terbium trifluoride can be used to prepare infrared optical materials. It has high infrared transparency and low scattering rate, making it an ideal choice for infrared window materials. With the development of infrared technology, the demand for terbium trifluoride will further increase. In addition, terbium trifluoride can also be used to prepare laser crystals. Crystals doped with terbium fluoride can produce tunable lasers, which can be used in fields such as laser radar and optical fiber communications. Therefore, terbium trifluoride has important application prospects in the field of optics.
[0003] At present, terbium trifluoride is mainly prepared by dry method. One method is to mix ammonium bifluoride and terbium oxide evenly and then react. This will lead to problems such as incomplete reaction and serious equipment corrosion, resulting in low purity of the produced terbium trifluoride. The other method is to prepare it by reacting anhydrous hydrogen fluoride with terbium oxide, which will result in serious equipment corrosion and low purity. Summary of the invention
[0004] In order to solve the technical problem that the existing method for preparing terbium trifluoride produces terbium fluoride with low purity, the present invention provides a method for preparing crystalline terbium trifluoride, which can produce terbium fluoride with a purity of more than 99.99%.
[0005] The technical solution of the present invention is:
[0006] A method for preparing crystalline terbium trifluoride, which is special in that it comprises the following steps:
[0007] Step 1, preparing high-purity terbium carbonate;
[0008] Step 1.1: dissolving high-purity hydrated terbium nitrate crystals into a terbium nitrate solution with a specific gravity of 1.15-1.2, adding the solution into a pure ammonium carbonate solution, adjusting the pH to 8-9, heating the solution to above 80° C. (stirring and aging at this temperature can reduce the bound water in the molecule, facilitating production operation), stirring the solution for 1-2 hours, and obtaining a high-purity terbium carbonate synthetic solution; the high-purity hydrated terbium nitrate crystals are hydrated terbium nitrate crystals with iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents all less than 0.2 ppm. The pure ammonium carbonate solution is an ammonium carbonate solution that does not contain mechanical impurities and trace insolubles, and the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium is less than 0.1ppm; in this step, the high-purity hydrated terbium nitrate crystals are dissolved in high-purity water to a specific gravity of 1.15-1.2 because too small a specific gravity will lead to too low a production capacity, and too large a specific gravity will form a hydrate and cannot be operated; the pH value is adjusted to 8-9 because if the pH value is not within this range, the yield of terbium salt will be low.
[0009] Step 1.2: centrifuging the high-purity terbium carbonate synthesis solution while hot, washing with water, controlling the nitrate content to be less than 0.02%, and the iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0010] Step 2, preparing high-purity terbium trifluoride;
[0011] Using electronic grade hydrofluoric acid and the high-purity terbium carbonate to react with heat preservation and stirring to drive out carbonate ions to obtain a terbium trifluoride synthesis liquid, and then centrifuging and washing to obtain a terbium trifluoride filter cake;
[0012] Step 3, secondary fluorination and drying;
[0013] The terbium trifluoride filter cake is added to the ammonium bifluoride solution, concentrated and crystallized, and filtered to obtain terbium trifluoride wrapped by ammonium bifluoride crystals, and the terbium trifluoride wrapped by the ammonium bifluoride crystals is dried and fluorinated at low temperature, and then gradient dried under nitrogen protection to obtain a terbium fluoride product. The obtained terbium fluoride product is tested, and the test data show that the content of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium is less than 0.5ppm, iron is less than 1ppm, oxygen is less than 0.03%, and the purity is more than 99.99%, which meets the standard of crystal-grade terbium trifluoride.
[0014] Furthermore, the preparation method of high-purity hydrated terbium nitrate crystals in step 1.1 is specifically as follows:
[0015] First, analytical pure nitric acid is added to a reaction kettle, and then pure water is added in a ratio of 1:1 to dilute the mixture. Then, high-purity 4N terbium oxide is slowly added thereto, and the molar ratio of nitric acid to terbium is 3:1. The pH is adjusted to 1-1.5, the temperature is raised to 60-80° C., and the mixture is stirred for reaction for 30-60 minutes. The supernatant is filtered using a filter element with a filtration accuracy of at least 1 μm to obtain a terbium nitrate solution.
[0016] Then, the terbium nitrate solution is heated to 100-110° C., and is concentrated under slight negative pressure (the slight negative pressure here refers to the negative pressure amount that the negative pressure gauge slightly swings and the value cannot be read). After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature is lowered to 20-30° C. (the crystallization yield will be reduced if the temperature is higher than this, and additional refrigeration equipment is required if the temperature is lower than this, which increases the cost), the crystals are fished out, centrifuged and dried, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0017] Furthermore, the preparation method of the pure ammonium carbonate solution in step 1.1 is specifically as follows:
[0018] Reagent-grade ammonium carbonate is dissolved in high-purity water to a mass fraction of 15-20%, and filtered to remove mechanical impurities and trace insolubles. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution are controlled to be less than 0.1 ppm to obtain a pure ammonium carbonate solution.
[0019] Optimally, reagent-grade ammonium carbonate is dissolved to a mass fraction of 20%. On the one hand, if the mass fraction is too large, a lot of smoke will appear, which is difficult to operate. At the same time, the concentration of terbium carbonate prepared later will be too high and the viscosity will be too high, which is difficult to operate. On the other hand, if the mass fraction is too small, the production capacity will be reduced.
[0020] Furthermore, in step 1.2, 800 mesh filter cloth is used and centrifugation is performed at a speed of 1000 rpm.
[0021] Furthermore, step 2 is specifically as follows:
[0022] Step 2.1 Add 40-50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 60° C. or above, add the high-purity terbium carbonate obtained in step 1.2, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1-1.5, heat it to 80-100° C., stir and react for 2-3 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0023] Step 2.2: The terbium trifluoride synthesis liquid is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth, and then washed with hot water to remove free acid, thereby obtaining a terbium trifluoride filter cake.
[0024] Furthermore, step 3 is specifically as follows:
[0025] Step 3.1 Add analytical pure ammonia water to electronic grade hydrofluoric acid with a mass fraction of 20-50%, with the molar ratio of hydrofluoric acid to ammonia water being 2:1, to obtain an ammonium bifluoride solution;
[0026] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2 to the ammonium bifluoride solution, wherein the molar ratio of terbium trifluoride to ammonium bifluoride is 1:1, and concentrating and crystallizing the solution. After a large amount of crystals appear, the solution is filtered to obtain terbium trifluoride encapsulated by ammonium bifluoride crystals;
[0027] Step 3.3: Dry and fluorinate the terbium trifluoride wrapped by the ammonium bifluoride crystals at 120-150° C. for 1-2 hours to remove excess water while allowing the ammonium bifluoride to melt and more evenly wrap the terbium trifluoride. Dehydrate the terbium trifluoride under the protection of ammonium fluoride to prevent oxidation and hydrolysis during the drying process. Then, dry the terbium trifluoride at 500-600° C. for 1-2 hours under nitrogen protection to further dehydrate and remove most of the ammonium bifluoride. Then, heat the terbium trifluoride to 900-1000° C. and dry the terbium trifluoride for 1-2 hours to remove impurities in the material that have not been removed in the previous temperature zone, thereby obtaining a finished terbium fluoride product.
[0028] The present invention also provides a crystalline terbium trifluoride, which is special in that it is prepared by the above method.
[0029] The advantages of the present invention are:
[0030] 1. The present invention can industrially produce terbium trifluoride with a purity of more than 99.99%, wherein the contents of cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all less than 0.5 ppm, the contents of iron are less than 1 ppm, the contents of oxygen are less than 0.03%, and the purity is more than 99.99%, which meets the standards of crystal-grade terbium trifluoride.
[0031] 2. The present invention adopts a wet reaction in the production process. After the impurities of the raw materials are removed, the reaction kettle can be made of enamel and polytetrafluoroethylene materials according to its properties to avoid corrosion problems of equipment during the reaction; the drying step adopts gradient drying, and each temperature zone adopts polytetrafluoroethylene, alloy, and platinum crucibles respectively to avoid equipment corrosion and pollution, thereby further improving the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD pattern of terbium trifluoride prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The present invention is conceived as follows:
[0034] The main difficulty in preparing crystal-grade materials is how to reduce the oxygen content. In order to solve this problem, after preparing terbium trifluoride, the present invention uses secondary fluorination to make ammonium bifluoride evenly wrap terbium trifluoride, and then performs gradient drying to prevent oxidation and hydrolysis during the drying process, thereby reducing the oxygen content; during gradient drying, ammonium bifluoride is first used to protect terbium trifluoride in a low temperature section (120-150° C.) to remove most of the water, and then high-purity nitrogen is used for protection in a high temperature section, and at the same time, the ammonium bifluoride remaining in the material can also prevent hydrolysis to a certain extent.
[0035] The reaction equation involved in the present invention is:
[0036] 2Tb(NO3)3+3(NH4)2CO3=====Tb2(CO3)3+6NH4NO3
[0037] Tb2(CO3)3+6HF====2TbF3+3H2O+3CO2
[0038] The present invention is further described in detail below by way of examples.
[0039] Example 1
[0040] This example prepares crystalline terbium trifluoride by the following steps:
[0041] Step 1, preparing high-purity terbium carbonate;
[0042] Step 1.1: terbium salt purification;
[0043] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a ratio of 1:1 to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 1.3, the temperature was raised to 70°C, and the reaction was stirred for 60 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0044] Then, the terbium nitrate solution is heated to 105° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 20° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0045] Step 1.2 ammonium carbonate purification;
[0046] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 20%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0047] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.18, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 8.8, heating to above 80° C., stirring and reacting for 2 hours to obtain a high-purity terbium carbonate synthetic solution;
[0048] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0049] Step 2, preparing high-purity terbium trifluoride;
[0050] Step 2.1 Add 50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 60° C., add the high-purity terbium carbonate obtained in step 1.4, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1.3, heat it to 80° C., stir and react for 3 hours to remove the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0051] Step 2.2: The terbium trifluoride synthesis liquid is pumped into a centrifuge, and centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth, and then slightly washed with hot water to remove free acid, thereby obtaining a terbium trifluoride filter cake;
[0052] Step 3, secondary fluorination and drying;
[0053] Step 3.1 Take 50% electronic grade hydrofluoric acid by mass and add it to a tetrafluoroethylene beaker, dilute it to a mass fraction of 25%, add analytical pure ammonia water thereto, the molar ratio of hydrofluoric acid to ammonia water is 2:1, and obtain an ammonium bifluoride solution;
[0054] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the ammonium bifluoride solution obtained in step 3.1, wherein the molar ratio of terbium trifluoride to ammonium bifluoride is 1:1, and concentrating and crystallizing the mixture. After a large amount of crystals appear, filtering is performed to obtain terbium trifluoride encapsulated by ammonium bifluoride crystals;
[0055] Step 3.3: Add the terbium trifluoride wrapped in ammonium bifluoride obtained in step 3.2 into a tetrafluoroethylene crucible, dry and fluorinate at 120°C for 1.5 hours, then transfer to a platinum crucible, place in a tube furnace under nitrogen protection, dry at 550°C for 2 hours, then heat to 1000°C and dry for 2 hours to obtain the finished terbium fluoride. After XRD detection, the product is identified as terbium trifluoride, and the corresponding XRD pattern is as follows: Figure 1 As shown; after testing, the content of cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the finished terbium fluoride is less than 0.5ppm, iron is less than 1ppm, oxygen is less than 0.03%, and the purity is more than 99.99%, which meets the standard of crystal-grade terbium fluoride.
[0056] Example 2
[0057] In this example, terbium fluoride was prepared by the following steps
[0058] Step 1, preparing high-purity terbium carbonate;
[0059] Step 1.1: terbium salt purification;
[0060] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a ratio of 1:1 to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 1, the temperature was raised to 80°C, and the reaction was stirred for 50 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0061] Then, the terbium nitrate solution is heated to 110° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 25° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0062] Step 1.2 ammonium carbonate purification;
[0063] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 15%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0064] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.19, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 8.6, heating to above 80° C., stirring and reacting for 1.5 hours to obtain a high-purity terbium carbonate synthetic solution;
[0065] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0066] Step 2, preparing high-purity terbium trifluoride;
[0067] Step 2.1 Add 40% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to above 60° C., add the high-purity terbium carbonate obtained in step 1.4, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1.2, heat it to 90° C., keep it warm and stir it for 2.5 hours, drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0068] Step 2.2: The terbium trifluoride synthesis liquid is pumped into a centrifuge, and centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth, and then slightly washed with hot water to remove free acid, thereby obtaining a terbium trifluoride filter cake;
[0069] Step 3, secondary fluorination and drying;
[0070] Step 3.1 Take 50% electronic grade hydrofluoric acid by mass and add it to a tetrafluoroethylene beaker, dilute it to a mass fraction of 20%, add analytical pure ammonia water thereto, the molar ratio of hydrofluoric acid to ammonia water is 2:1, and obtain an ammonium bifluoride solution;
[0071] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the ammonium bifluoride solution obtained in step 3.1, wherein the molar ratio of terbium trifluoride to ammonium bifluoride is 1:1, and concentrating and crystallizing the mixture. After a large amount of crystals appear, filtering is performed to obtain terbium trifluoride encapsulated by ammonium bifluoride crystals;
[0072] Step 3.3: Add the terbium trifluoride wrapped in ammonium bifluoride obtained in step 3.2 to a tetrafluoroethylene crucible, dry and fluorinate at 130°C for 2 hours, then transfer to a platinum crucible, put it in a tubular furnace under nitrogen protection, dry it at 580°C for 1.5 hours, and then heat it to 900°C for 2 hours to obtain a terbium fluoride product. After testing, the cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents in the terbium fluoride product are all less than 0.5ppm, iron is less than 1ppm, oxygen is less than 0.03%, and the purity is more than 99.99%, which meets the crystal-grade terbium fluoride standard.
[0073] Example 3
[0074] In this embodiment, terbium fluoride is prepared by the following steps:
[0075] Step 1, preparing high-purity terbium carbonate;
[0076] Step 1.1: terbium salt purification;
[0077] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a ratio of 1:1 to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 1.5, the temperature was raised to 60°C, and the reaction was stirred for 40 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0078] Then, the terbium nitrate solution is heated to 100° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 30° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0079] Step 1.2 ammonium carbonate purification;
[0080] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 18%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0081] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.2, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 8, heating to above 80° C., stirring and reacting for 1 hour, and obtaining a high-purity terbium carbonate synthetic solution;
[0082] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0083] Step 2, preparing high-purity terbium trifluoride;
[0084] Step 2.1: Add 45% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to above 60° C., add the high-purity terbium carbonate obtained in step 1.4, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1, heat it to 85° C., stir and react for 2 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0085] Step 2.2: The terbium trifluoride synthesis liquid is pumped into a centrifuge, and centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth, and then slightly washed with hot water to remove free acid, thereby obtaining a terbium trifluoride filter cake;
[0086] Step 3, secondary fluorination and drying;
[0087] Step 3.1 Take 50% electronic grade hydrofluoric acid by mass and add it to a tetrafluoroethylene beaker, dilute it to a mass fraction of 40%, add analytical pure ammonia water thereto, the molar ratio of hydrofluoric acid to ammonia water is 2:1, and obtain an ammonium bifluoride solution;
[0088] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the ammonium bifluoride solution obtained in step 3.1, wherein the molar ratio of terbium trifluoride to ammonium bifluoride is 1:1, and concentrating and crystallizing the mixture. After a large amount of crystals appear, filtering is performed to obtain terbium trifluoride encapsulated by ammonium bifluoride crystals;
[0089] Step 3.3: Add the terbium trifluoride wrapped in ammonium bifluoride obtained in step 3.2 to a tetrafluoroethylene crucible, dry and fluorinate at 150°C for 2 hours, then transfer to a platinum crucible, put it in a tubular furnace under nitrogen protection, dry it at 600°C for 1 hour, and then heat it to 950°C for 1.5 hours to obtain a terbium fluoride product. After testing, the cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents in the terbium fluoride product are all less than 0.5ppm, iron is less than 1ppm, oxygen is less than 0.03%, and the purity is more than 99.99%, which meets the crystal-grade terbium fluoride standard.
[0090] Example 4
[0091] In this embodiment, terbium fluoride is prepared by the following steps:
[0092] Step 1, preparing high-purity terbium carbonate;
[0093] Step 1.1: terbium salt purification;
[0094] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a 1:1 ratio to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 1.4, the temperature was raised to 65°C, and the reaction was stirred for 30 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0095] Then, the terbium nitrate solution is heated to 110° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 30° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0096] Step 1.2 ammonium carbonate purification;
[0097] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 18%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0098] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.15, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 9, heating to above 80° C., stirring and reacting for 1 hour, and obtaining a high-purity terbium carbonate synthetic solution;
[0099] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0100] Step 2, preparing high-purity terbium trifluoride;
[0101] Step 2.1 Add 45% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to above 60° C., add the high-purity terbium carbonate obtained in step 1.4 thereto, the molar ratio of hydrofluoric acid to terbium being 3:1, adjust the pH to 1.5, heat to 100° C., stir and react for 3 hours under heat preservation, drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0102] Step 2.2: The terbium trifluoride synthesis liquid is pumped into a centrifuge, and centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth, and then slightly washed with hot water to remove free acid, thereby obtaining a terbium trifluoride filter cake;
[0103] Step 3, secondary fluorination and drying;
[0104] Step 3.1: Add 50% electronic grade hydrofluoric acid into a tetrafluoroethylene beaker, add analytical pure ammonia water thereto, the molar ratio of hydrofluoric acid to ammonia water being 2:1, and obtain an ammonium bifluoride solution;
[0105] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the ammonium bifluoride solution obtained in step 3.1, wherein the molar ratio of terbium trifluoride to ammonium bifluoride is 1:1, and concentrating and crystallizing the mixture. After a large amount of crystals appear, filtering is performed to obtain terbium trifluoride encapsulated by ammonium bifluoride crystals;
[0106] Step 3.3: Add the terbium trifluoride wrapped in ammonium bifluoride obtained in step 3.2 to a tetrafluoroethylene crucible, dry and fluorinate at 135°C for 1 hour, then transfer to a platinum crucible, put it in a tubular furnace under nitrogen protection, dry it at 500°C for 2 hours, and then heat it to 920°C and dry it for 1 hour to obtain a finished terbium fluoride product. After testing, the content of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the finished terbium fluoride is less than 0.5ppm, iron is less than 1ppm, oxygen is less than 0.03%, and the purity is more than 99.99%, which meets the standard of crystal-grade terbium fluoride.
Claims
1. A method for preparing crystalline terbium trifluoride, characterized in that: The following steps are involved: Step 1, preparing high-purity terbium carbonate; Step 1.1: dissolving high-purity hydrated terbium nitrate crystals into a terbium nitrate solution with a specific gravity of 1.15-1.2, adding the solution into a pure ammonium carbonate solution, adjusting the pH to 8-9, heating the solution to 80°C or above, stirring the solution for 1-2 hours, and obtaining a high-purity terbium carbonate synthetic solution; the high-purity hydrated terbium nitrate crystals are hydrated terbium nitrate crystals with iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents all less than 0.2ppm; the pure ammonium carbonate solution is an ammonium carbonate solution free of mechanical impurities and trace insolubles, and with iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents all less than 0.1ppm; Step 1.2: centrifuging the high-purity terbium carbonate synthesis solution while hot, washing with water, controlling the nitrate content to be less than 0.02%, and the iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents to be less than 0.3 ppm, to obtain high-purity terbium carbonate; Step 2, preparing high-purity terbium trifluoride; Using electronic grade hydrofluoric acid and the high-purity terbium carbonate to react with heat preservation and stirring to drive out carbonate ions to obtain a terbium trifluoride synthesis liquid, and then centrifuging and washing to obtain a terbium trifluoride filter cake; Step 3, secondary fluorination; The terbium trifluoride filter cake is added to an ammonium bifluoride solution, concentrated and crystallized, and filtered to obtain terbium trifluoride wrapped by ammonium bifluoride crystals. The terbium trifluoride wrapped by the ammonium bifluoride crystals is dried and fluorinated at low temperature, and then gradient dried under nitrogen protection to obtain a terbium fluoride finished product.
2. The method for preparing crystalline terbium trifluoride according to claim 1, characterized in that: The preparation method of high-purity hydrated terbium nitrate crystals in step 1.1 is specifically as follows: First, analytical pure nitric acid is added to a reaction kettle, and then pure water is added in a ratio of 1:1 to dilute the mixture. Then, high-purity 4N terbium oxide is slowly added thereto, and the molar ratio of nitric acid to terbium is 3:
1. The pH is adjusted to 1-1.5, the temperature is raised to 60-80° C., and the mixture is stirred for reaction for 30-60 minutes. The supernatant is filtered using a filter element with a filtration accuracy of at least 1 μm to obtain a terbium nitrate solution. Then, the terbium nitrate solution is heated to 100-110° C. and concentrated under slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 20-30° C., the crystals are fished out and centrifuged to dry. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
3. The method for preparing crystalline terbium trifluoride according to claim 1, characterized in that: The preparation method of the pure ammonium carbonate solution in step 1.1 is specifically as follows: Reagent-grade ammonium carbonate is dissolved in high-purity water to a mass fraction of 15-20%, and filtered to remove mechanical impurities and trace insolubles. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution are controlled to be less than 0.1 ppm to obtain a pure ammonium carbonate solution.
4. The method for preparing crystalline terbium trifluoride according to claim 3, characterized in that: The preparation method of the pure ammonium carbonate solution in step 1.1 is specifically as follows: Reagent-grade ammonium carbonate is dissolved in high-purity water to a mass fraction of 20%, and filtered to remove mechanical impurities and trace insolubles. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution are controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained.
5. The method for preparing crystalline terbium trifluoride according to claim 1, characterized in that: In step 1.2, 800 mesh filter cloth is used and centrifugation is performed at a speed of 1000 rpm.
6. The method for preparing crystalline terbium trifluoride according to any one of claims 1 to 5, characterized in that: Step 2 is as follows: Step 2.1 Add 40-50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to above 60° C., add the high-purity terbium carbonate obtained in step 1.2, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1-1.5, heat it to 80-100° C., stir and react for 2-3 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution; Step 2.2: The terbium trifluoride synthesis liquid is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth, and then washed with hot water to remove free acid, thereby obtaining a terbium trifluoride filter cake.
7. The method for preparing crystalline terbium trifluoride according to claim 6, characterized in that: Step 3 is as follows: Step 3.1 Add analytical pure ammonia water to electronic grade hydrofluoric acid with a mass fraction of 20-50%, with the molar ratio of hydrofluoric acid to ammonia water being 2:1, to obtain an ammonium bifluoride solution; Step 3.2: adding the terbium trifluoride filter cake obtained in step 2 to the ammonium bifluoride solution, wherein the molar ratio of terbium trifluoride to ammonium bifluoride is 1:1, and concentrating and crystallizing the solution. After a large amount of crystals appear, the solution is filtered to obtain terbium trifluoride encapsulated by ammonium bifluoride crystals; Step 3.3: drying the terbium trifluoride wrapped by the ammonium bifluoride crystal at 120-150° C. for fluorination for 1-2 hours, and then drying at 500-600° C. for 1-2 hours under nitrogen protection, and then heating to 900-1000° C. for drying for 1-2 hours to obtain a finished terbium fluoride product.
8. The method for preparing crystalline terbium trifluoride according to claim 7, characterized in that: Step 3.1 and step 3.2 are reacted in a PTFE container. Step 3.3 is to first dry and fluorinate the terbium trifluoride wrapped in the ammonium bifluoride crystal in a PTFE crucible at 120-150°C, then transfer it into a platinum crucible, put it into a tubular furnace under nitrogen protection, first dry it at 500-600°C, and then heat it to 900-1000°C for drying.
9. A crystalline terbium trifluoride, characterized in that: The method is prepared by any one of claims 1 to 8.